Anaesthesia Management in Parturient with Peripartum Cardiomyopathy: A Case Report - Leo, Joseph Nelson; Aryasa, Tjahya; Senapathi, Tjokorda Gde Agung (Syntax Literate, 2024)
Peripartum cardiomyopathy (PPCM) is an idiopathic cardiomyopathy secondary to left ventricle systolic dysfunction towards the end of pregnancy or in the months following delivery. Generally, the clinical presentation and anaesthetic management principle are similar to heart failure due to other causes. We report a case of a 27-year-old woman with a diagnosis of first pregnancy, 34 weeks, single and viable fetus, with preeclampsia with severe presentation and lung oedema et causa PPCM planned to have an emergency cesarean section. Pre-anesthesia evaluation revealed physical status ASA III E with lung edema (SpO2 96% with NRM 10 lpm) and EF 38% from echocardiography. The surgery was done with a regional anaesthesia epidural on L1-L2 using bupivacaine 0.25% with lidocaine 1% volume 10 ml caudally and bupivacaine 0.25% volume 10 ml via the epidural catheter. During surgery, blood pressure drops and is manageable with vasopressor. After surgery, the mother and baby were stable. The patient was treated in intensive care for three days and then transferred to a general ward. PPCM is relatively rare. This case could be used as a reference in managing future PPCM cases.